2020
DOI: 10.1186/s12879-020-05196-z
|View full text |Cite
|
Sign up to set email alerts
|

Significance of sTREM-1 in early prediction of ventilator-associated pneumonia in neonates: a single-center, prospective, observational study

Abstract: Background: To evaluate whether soluble triggering receptor expressed on myeloid cells-1 (sTREM-1) can be used as an early predictor of ventilator-associated pneumonia (VAP). Methods: Ventilated neonatal patients admitted into the neonatology department between January 2017 and January 2018 were divided into VAP (n = 30) and non-VAP (n = 30) groups. Serum sTREM, procalcitonin (PCT), Creactive protein and interleukin-6 levels were measured at 0, 24, 72, and 120 h after initiation of mechanical ventilation (MV).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
(34 reference statements)
1
11
0
Order By: Relevance
“…The results of this study showed that the serum levels of IL-18 and sTREM-1 in the VAP group were higher than those in the non-VAP group, while the levels of CC16 in the VAP group were lower than those in the non-VAP group. This is consistent with the research conclusions of Zhao et al (19), indicating that serum IL-18, CC16, and sTREM-1 levels are related to the occurrence of VAP. In addition, the present study found that serum IL-18 and sTREM-1 levels in the high-risk group were higher than those in the intermediate-risk group and the low-risk group, while CC16 levels in the high-risk group were lower than those in the intermediate-risk group and the low-risk group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of this study showed that the serum levels of IL-18 and sTREM-1 in the VAP group were higher than those in the non-VAP group, while the levels of CC16 in the VAP group were lower than those in the non-VAP group. This is consistent with the research conclusions of Zhao et al (19), indicating that serum IL-18, CC16, and sTREM-1 levels are related to the occurrence of VAP. In addition, the present study found that serum IL-18 and sTREM-1 levels in the high-risk group were higher than those in the intermediate-risk group and the low-risk group, while CC16 levels in the high-risk group were lower than those in the intermediate-risk group and the low-risk group.…”
Section: Discussionsupporting
confidence: 93%
“…At the same time, the migration of inflammatory factor in the inflammatory part of the lung is closely related, which can reflect the severity of the infection in the body (17,18). Zhao et al have shown that sTREM-1 is a reliable predictor of VAP in neonates, and combined measurement of serum levels of sTREM-1 and PCT after 72 h of MV provided the most accurate prediction of VAP in neonatal patients (19).…”
Section: Discussionmentioning
confidence: 99%
“…Fungal infection has certain conditions, but it lacks characteristics and is difficult to diagnose, and the prognosis of patients is generally poor. Therefore, it is urgent to find more specific indicators in clinical practice, in order to improve the efficiency of diagnosis and guide clinical treatment [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Soluble triggering receptors expressed on myeloid cell-1 (sTREM-1) are an important inflammatory factor and index of oxidative stress. e increase of its concentration can lead to the activation of downstream inflammatory signaling pathways, improve the upregulation of effector factors such as interleukin-6, and cooperate with toll-like receptors to mediate the expansion of inflammatory response, thus promoting the progression of pulmonary infectious disease [12][13][14]. Among many chemokines and chemokine receptors, CXC chemokine ligand receptor-16 (CXCL-16)/CXCR6 is a pair of chemokine ligand-receptor pairs with unique functions.…”
Section: Introductionmentioning
confidence: 99%